A hidden pathophysiology of endolymphatic hydrops: case report of a patient with spontaneous intracranial hypotension presenting with sudden sensorineural hearing loss with vertigo - Kim, Jong Kwan; Lee, Ho Yun; Kim, Ha Youn; Kwak, Min Young (Frontiers in Neurology, 2024)
Spontaneous intracranial hypotension (SIH) is characterized by decreased cerebrospinal fluid (CSF) volume due to leakage through the dural membrane. We present the case of a patient with SIH manifested by fluctuating low-frequency hearing loss, tinnitus, and vertigo. In this patient, endolymphatic hydrops in the cochlea and saccule were visualized by means of a special sequence of inner ear magnetic resonance imaging scans, with a gadolinium-based contrast agent administered intravenously. Endolymphatic hydrops is a potential underlying pathophysiology of SIH-associated hearing impairment. We hypothesize that SIH may be a rare cause of endolymphatic hydrops.